Demarcation of Right of Way (ROW) and Re-Installation of Damaged Markers of Transmission Pipeline in Balochistan, Pakistan through Geomatics Technologies: A Case Study of Zarghun to Quetta High Pressure Natural Gas Supply - Zawwar Hussain,; Syed Ali Asad Naqvi,; Syed Jamil H. Kazmi,; Syed Ali Naqi,; Muhammad Haneef ,; Farina Zulfi, (Journal of Basic & Applied Sciences, 2015)
The alignment of gas pipelines in a rugged terrain has always been a serious challenge around the globe but they can be perfectly aligned with the help of Geo-Spatial technologies. When South Zarghun gas fields were discovered in Pakistan, gas transmission pipeline laying process between gas fields and Quetta city was as challenging task for the Government of Pakistan. Very rough terrain and extreme weather conditions especially in winter season were the two major constraints for the alignment of pipeline. Geomatics survey was essential before transmission pipeline construction work, done twice by private consultant in Pakistan’s local geographic coordinate system. SSGC took decision in 2006 for the construction of pipeline but unfortunately it could not be executed due to law & order situation in Pakistan especially in Balochistan province and later all bench marks of pipeline alignment route were vanished by the locals. In 2012, SSGC again started pipeline construction work on war steps. Previous pipeline alignment survey was converted into existing SSGC’s GIS coordinate system i.e. UTM Zone 42 WGS84 using ESRI ArcGIS software. Identification & re-installation of all bench marks and re-routing of pipeline were done by SSGC GIS survey team with the help of global positioning system (GPS) and satellite data. Finally, right of way (ROW) of transmission pipeline from Zarghun gas fields to Quetta city was designed and produced in the form of GIS map for pipeline construction activities.